Miss me with that : hot takes, helpful tidbits, and a few hard truths - Lindsay, Rachel, 1985-; Quintero, Sofia (Ballantine Books, 2022)
"A candid, witty, and inspiring collection of essays from The Bachelor's first Black Bachelorette, exploring everything from relationships and love to politics and race. Extra correspondent and Higher Learning co-host Rachel Lindsay originally rose to prominence as the first Black Bachelorette and has since become one of the franchise's most well-known figures. For the first time, Rachel opens up about what it meant to be the first Black lead on ABC's hit show and reveals everything about her life off-camera, from her childhood growing up in Dallas, Texas, as the daughter of a U.S. District Judge to her disastrous dating life prior to going on The Bachelor, to her career in law, her evolving female friendships, and her decision to become a reality TV contestant. She also brings her sharp wit and keen intellect to weigh in on issues such as the lack of diversity in reality television and the importance of political engagement, protest, voting, and the Black Lives Matter movement. Told in the down-to-earth, no-nonsense voice she's become known for, Lindsay's collection will provide an intimate look at the life of one of reality TV's most beloved and outspoken stars, as well as advice and inspiration that will make her a role model for anyone who has ever tried to make sense of love and life and lost their way trying to do so"--